FAKTOR PENGHAMBAT PEMENUHAN HAK KESEHATAN REPRODUKSI PENYANDANG DISABILITAS (STUDI PADA REMAJA SMP DI SLB NEGERI BANTUL YOGYAKARTA) - HERI PUSPITO; Hartuti Purnaweni; Sri Achadi Nugraheni (VISIKES: Jurnal Kesehatan Masyarakat, 2019)
Bantul was made Regulation No. 11 of 2015 to fulfill the rights of persons with disabilities. They are still didnâ€™t get the justice while regional regulations come off. This study aims to obtain an overview the barrier factors of policies implementation related reproductive rights of health in youth with disabilities in Bantul Regency. This qualitative research was conductedÂ  in Government Bantul of D.I Yogyakarta province in June-July 2019. Data collection techniques with in-depth interviews, observation and document study. The implementation regulation No.11 of 2015 in Bantul has not proceeded as expected, efforts to fulfill the rights of persons with disabilities, both promotive and preventive, have yet to be achieved. Various factors that inhibit include the communication, resources, disposition, coordination across organization, organizing and interpretation. The reproductive rights of adolescents with disabilities in Bantul district encountered various obstacles. It should be given main of purpose and fungtion from the contents of regulation No. 11 of 2015 in to the implementers, established a system of organizing and interpreting policy stakeholders and regional unit government, increasing socialization, communication, resources, relations between organizations and related stakeholders.